Anayzing the Capacity Utilization Rate of Traction Motor Drives in Electric Vehicles with Real World Driving Cycles - Ozdemir, Sadik; Elma, Onur; Acar, Fatih; Selamogullari, Ugur S. (IEEE, 2014)
This study presents real word drive cycles in Istanbul, Turkey and analyzes the impact of these real road conditions on the performance of an electric vehicle. For this purpose, five different drive cycles has been obtained by collecting data for different traffic conditions in Istanbul. Both the velocity of the vehicle and the gradient of the road are considered. Also, a simplified dynamic vehicle model is developed to estimate the traction power requirement of drive-train of the vehicle during start up and when it is in motion.
Keywords: Electric vehicles (EV); Driving Cycle; Energy Efficiency; Engineering; Transportation